Fostering Grade 10 Students' Speaking Confidence through Procedure Text Videos: A Descriptive Qualitative Study at SMKS Jayanegara Ambon - Umarella, Rahmatul Firdausa; Kainta, Erwin (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2025)
This study explores how video-based procedure text tasks can foster speaking confidence among senior high school students learning English. Speaking is frequently the language skill that causes the anxiety for learners, particularly in environments where students fear making mistakes or being judged. By integrating structured genre pedagogy with video production, this research investigates how students engage with language in a low-pressure setting that encourages rehearsal, reflection, and self-expression. Conducted in a Grade 10 classroom at SMKS Jayanegara Ambon, the study employed semi-structured interviews, observation checklists, and teacher field notes to capture students’ emotional and behavioral responses. Findings reveal that most students experienced increased self-awareness, reduced anxiety, and greater motivation when completing video tasks. The procedure text format provided a clear linguistic framework, helping students organize their thoughts and deliver instructions with clarity. Video recording allowed students to practice and revise their speech, minimizing the fear associated with live performance. While some students faced challenges related to editing, pronunciation, and group collaboration, the overall impact on speaking confidence was positive. The study demonstrates that combining procedural language with video-based learning offers a meaningful way to support oral communication skills. This approach encourages autonomy, creativity, and emotional readiness, making it a valuable strategy for enhancing speaking instruction in English classrooms.